2020
DOI: 10.1007/s10549-020-05988-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of monitoring techniques on progression to chronic breast cancer-related lymphedema: a meta-analysis comparing bioimpedance spectroscopy versus circumferential measurements

Abstract: Background Chronic breast cancer-related lymphedema (BCRL) is a potentially serious complication following treatment. Monitoring for progression to BCRL may allow for earlier detection and intervention, reducing the rate of progression to chronic BCRL. Therefore, the purpose of this meta-analysis is to evaluate the impact of monitoring techniques on the incidence of chronic BCRL among patients monitored by bioimpedance spectroscopy (BIS) and circumference as compared to background rates. Methods Eligible peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…Our findings are consistent with previous prospective studies which found that use of BIS as part of prospective surveillance resulted in a persistent C-BCRL rate of only 6%. 26 The final results of the study, confirm the significantly lower rates of trigger with BIS as compared to TM (20.7% vs 27.5%, P=.011) as seen at the interim analysis. 28,29,30 Critical knowledge to inform the optimal method of prospective surveillance was also generated in this study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our findings are consistent with previous prospective studies which found that use of BIS as part of prospective surveillance resulted in a persistent C-BCRL rate of only 6%. 26 The final results of the study, confirm the significantly lower rates of trigger with BIS as compared to TM (20.7% vs 27.5%, P=.011) as seen at the interim analysis. 28,29,30 Critical knowledge to inform the optimal method of prospective surveillance was also generated in this study.…”
Section: Discussionsupporting
confidence: 65%
“…12,25 This is supported by a metaanalysis of more than 67,000 women and 50 studies that found that use of BIS reduced annualized and cumulative incidence of C-BCRL as compared to TM or background studies, though not controlling for intervention protocols as the current study did. 26 These consistent significant findings are likely related to the ability of BIS to detect an increase in extracellular fluid, as opposed to TM's ability to only detect an increase in whole arm volume. Thus, BIS serves as a better screening method to determine who will best benefit from a prevention intervention and achieve reversal of the S-BCRL process that can lead to C-BCRL.…”
Section: Discussionmentioning
confidence: 82%
“…This stands in contrast to findings from a recent systematic review supporting the use of BIS (81% reduction in risk of chronic BCRaL compared with surveillance programs using circumference measurements). 53 However, this review had considerable methodologic limitations, and conclusions were not supported by the data presented. 54,55 Conversely, our results do not lend support for the superiority of BIS over other measurement methods but instead highlight the need for consensus on BCRaL assessment and associated criteria.…”
Section: Discussionmentioning
confidence: 85%
“…BIS was the most frequently used measurement method and is considered to be well suited for early diagnosis of BCRaL. 53 However, six different diagnostic criteria for triggering intervention were applied. The general notion is that a lower criterion (eg, increase of two SD instead of three SD) is preferred as it provides better sensitivity to detect BCRaL.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of bioimpedance remains contentious in the screening of lymphedema [12,14,[28][29][30][31][32][33][34][35]. Previous studies demonstrated a low sensitivity (7.5-64%) of BIS in diagnosing breast cancer-related lymphedema [12,14,34,35], which was associated with 61-71% of positive predictive value and 67-70% of negative predictive value [35].…”
Section: Discussionmentioning
confidence: 99%